Online Interventions to Improve Mental Health of Pediatric, Adolescent, and Young Adult Cancer Survivors: A Systematic Review and Meta-Analysis - Chandeying, Nutthaporn; Thongseiratch, Therdpong (Frontiers in Psychiatry, 2021)
Objective: Over the last ten years, online interventions to improve mental health have increased significantly. This study’s primary objective was to determine the effectiveness of online interventions in improving the mental health of pediatric, adolescent, and young adult (PAYA) cancer survivors. The secondary objective was to identify the independent variables associated with online intervention efficacy for mental health improvement. Methods: On June 25 – 30, 2021, we searched the Medline, PsycINFO, EMBASE, and Cochrane databases for eligible English language publications that reported randomized controlled trials of online interventions aimed at improving mental health among PAYA cancer survivors. The results were analyzed using a systematic review and a three-level meta-analysis. Results: Thirteen studies met the inclusion criteria. In six (42%) studies, the intervention focused on physical activity enhancement, while ten (77%) studies used self-directed interventions. Online interventions were more efficacious, compared to control conditions, in improving sleep g = 0.35 (95% CI 0.04 – 0.66) and psychological well-being g = 0.32 (95% CI 0.09 – 0.56), but not for reducing the symptoms of depression g = 0.17 (95% CI -0.13 – 0.47), anxiety g = 0.05 (95% CI -0.15 – 0.25), and pain g = 0.13 (95% CI -0.13 – 0.39). Conclusion: Online interventions were generally effective in improving mental health in PAYA cancer survivors, although negative results were found in some critical outcomes. More high-quality evidence is needed for definite conclusions to be drawn.